(untitled) (KULT_online, 2011)
Based upon case studies from the fields of media production, literature, theatre, film and television, visual arts, and fashion, this volume questions the political meanings of subversive aesthetics today. Through the exemplary analysis of diverse strategies and aporias that surround them, the authors offer proposals for redefining the notion of subversion. This redefinition includes pluralization of the notion of subversion, focusing on its productive rather than disruptive dimension, and self-critical engagement with subversive tropes.